Pengaruh Pemberian Pupuk Kompos Dan Pupuk Green Tonik Terhadap Pertumbuhan Dan Hasil Tanaman Cabai Rawit (Capsicum frustescens L) Varietas Bhaskara - Ndaru Kuncoro; Tutik Nugrahini; Mahdalena Mahdalena (Universitas Widya Gama Mahakam, 2017)
The Influence of Compost Fertilizer And Grenn Tonic Fertilizer On The Growth And Results Of Rawit Chili Plants (Capsicum frustescens L) Bhaskara Varieties. The purpose of this research is to know the response of the use of compost fertilizer, Green Tonik liquid fertilizer and the interaction between compost fertilizer and Green Tonik liquid fertilizer on the growth and yield of pepper plant. The study was carried out for approximately 4 months, starting from July to October 2015, the research site at Jl. Thoyib Hadiwijaya Sempaja Timur, North Samarinda, East Kalimantan Province. The study was carried out for approximately 4 months, starting from July to October 2015, the research site at Jl. Thoyib Hadiwijaya Sempaja Timur, North Samarinda, East Kalimantan Province. This research method used Randomized Block Design with 4x4 factorial analysis consisting of 3 replications. The first factor is compost (k) consisting of 4 levels: k0: (control), k1: 50 g / polybag, k2: 100 g / polybag and k3: 150 g / polybag and second factor is Grenn Tonic (g) which consists of 4 levels: g0: (control), g1: 1.5ml / liter of water, g2: 3 ml / liter of water and g3: 4.5 ml / liter of water. The results of the compost fertilizer (k) showed that the effect was very significant on the average height and diameter of the plants at the age of 27 days HST, 40 HST and 53 HST as well as the average of crop yields, the highest crop yield on the treatment k2. The Green Tonic fertilizer treatment (g) showed that significantly affected the mean height and diameter of the plants at 27 days of HST, 40 HST and 53 HST as well as the average crop yield, the highest crop yield on treatment g2. In the second interaction treatment of compost (k) and Green Tonic (g) fertilizer had no significant effect on average of plant height increase, early age of flower, early age of harvest and fruit weight.